Gue, Saya, Aku, Kita: Person Deictic Comparison between Male and Female Indonesian Food Vloggers - Indarti, Dwi (Journal of Languages and Language Teaching, 2023)
YouTubers, content creators, or vloggers link in some way to influence their viewers. Therefore, the use of creative languages and a good linguistic approach is crucial to convey the content of the videos. Deictic expression is a common and a universal feature in regular conversation as well as in written productions. Deixis features a word or a phrase that points out people as person deixis, time as temporal deixis, or place as spatial deixis. This study analyzes and compares the use of person deictic expressions from six videos taken from three Indonesian male food vloggers and three Indonesian female food vloggers who have the most subscribers. The findings show that there is a difference between Indonesian male and female food vloggers. While Indonesian male food vloggers are mostly use informal person deictic expression gue (English: I, informal style), Indonesian female food vloggers use formal-polite person deictic expression aku, saya (English: I, formal style). They also use kita (English: inclusive-we) to minimize the distance between them and the viewers, indicating that they are having the same experiences. The findings could help the readers and the YouTube viewers to understand the function of person deictic expression that is to place the food vloggers at the center of the situation